Rede e apoio social da família no cuidado à criança com paralisia cerebral - Dantas, Meryeli Santos de Araújo (2017)
Introduction: Cerebral Palsy is a non-progressive clinical condition of the immature brain that affects the development of movement and posture. Objective: To understand the perception of the family of children with cerebral palsy about the network and social support. Method: Qualitative study, approved by the opinion 1,157,717, CAAE 46087015.5.0000.5188. The study was carried out in a school clinic and a reference institution in the State of Paraíba, with nine mothers and one father, through a talking map, ecomap and semi-structured interview, from October 2015 to March 2016. Interpretation of the data was performed By thematic analysis and based on the concepts of Alterity, Face and Corresponsabilization of the Other, described by Emmanuel Lévinas.Results: The therapeutic itinerary begins in the intercurrences in the childbirth when the family searches for specialists to elucidate the diagnosis. In the absence of this information, it builds the itinerary by itself, supported by the opinion of the community and of people who have followed similar paths. In illness situations, families prefer emergency services that they deem more effective than services of the family health strategy. With the growth of the child new demands arise, for example the need for care by specialists such as orthopedist, physiotherapist, speech therapist, changing the routine of treatment. The role of the mother has been responsible for building the network and articulation between the different professionals and services. Many people in the network provide emotional support, but instrumental care is the responsibility of the mother who is physically and emotionally overwhelmed. With the time and growth of the child the people who exercised a relationship of support begin to move away weakening the bonds. Final considerations: Although the network and social support are important tools to assist in coping with chronic child illness and family restructuring, the network of families of children with cerebral palsy has been small and fragile, and the assistance received is insufficient to meet the needs of the family.